Nootropic Activity of Leaf Extract of Anogessius latifolia - Hemamalini, K.; Lakshmi Narasimha Reddy, N.; Praveen Kumar Reddy, S.; Lokesh, K.V.; Maalu, G. (Asian Journal of Chemistry, 2011)
Nootropic effect of methanolic and chloroform extracts of Anogessius latifolia was evaluated by using elevated plus maze and diazepam induced amnesia models. Piracetam was used as the standard drug. A significant increase in inflexion ratio was recorded in elevated plus maze and diazepam induced amnesia models. The results indicate that nootropic activity observed with methanolic extract and chloroform extract of leaf of Anogessius latifolia could be through improved learning and memory either by augmenting the noradrenaline transmission or by interfering with 5-hydroxytryptamine (5-HT) release. Further, the extracts neither facilitated nor blocked release of the dopamine. Thus methanolic extract and chloroform extract elicited significant nootropic effect in mice and rats by interacting with cholinergic, GABAnergic, adrenergic and serotonergic systems. Phyto constituents like flavonoids have been reported for their nootropic effect and these are present in both methanolic extract and chloroform extract of leafs of Anogessius latifolia and these active principles may be responsible for nootropic activity.